LIVING LAB INNOVATION METHODOLOGIES - Proenca, joaquin Carvalho (Caderno de Administração, 2020)
An innovation program in a Living Lab in Colombia designed, developed and implementednew management practical and structured approach. The innovation program consisted of four blocks and it was chosen to create not only a new products and services portfolio, but new business model architecture and modular design and redesign in just 10 weeks. Data collection including business diagnosis, business context analysis, user observation, external interviews occurred in the first six weeks, while generation and validation of ideas over the last four weeks. The conditions of this program (based on learning, creating and experimentation processes within real world settings) helped companies to know in what stage of innovation they are or their business innovation potential. Further, it gives us clues about what business models innovation do in management theory questioning that innovative business models are in fact what matters and the sole model for innovation.